2013
DOI: 10.1074/jbc.m112.441949
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Progranulin Is a Homodimer and Is Not a Component of High Density Lipoproteins (HDL)

Abstract: Background: Progranulin is a secreted, anti-inflammatory glycoprotein, suggested to be a component of high density lipoproteins (HDL). Results: Studies in cells and plasma revealed secreted progranulin exists as a homodimer, does not bind lipids, and is not detected on HDL. Conclusion: Secreted progranulin exists as a homodimer and is not an HDL component. Significance: These data provide insights into the molecular properties of secreted progranulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
1
25
2
2
Order By: Relevance
“…It has been revealed that fasting blood sugar regulation is more related to waist circumference [43]. Another study has exhibited that plasma progranulin levels were positively correlated with fasting plasma glucose, waist circumferences and LDL-cholesterol and triglyceride levels and negatively correlated to HDLcholesterol, with HbA1c acting as an independent predictor of plasma progranulin levels [44] which was not in agreement with our findings (data not shown). Progranulin levels found in this study were higher than in the study done on a Chinese population [44].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It has been revealed that fasting blood sugar regulation is more related to waist circumference [43]. Another study has exhibited that plasma progranulin levels were positively correlated with fasting plasma glucose, waist circumferences and LDL-cholesterol and triglyceride levels and negatively correlated to HDLcholesterol, with HbA1c acting as an independent predictor of plasma progranulin levels [44] which was not in agreement with our findings (data not shown). Progranulin levels found in this study were higher than in the study done on a Chinese population [44].…”
Section: Discussioncontrasting
confidence: 55%
“…Another study has exhibited that plasma progranulin levels were positively correlated with fasting plasma glucose, waist circumferences and LDL-cholesterol and triglyceride levels and negatively correlated to HDLcholesterol, with HbA1c acting as an independent predictor of plasma progranulin levels [44] which was not in agreement with our findings (data not shown). Progranulin levels found in this study were higher than in the study done on a Chinese population [44]. Various other studies also represented the positive association between progranulin and components of the metabolic syndrome including insulin resistance, obesity and dyslipidemia [34, 45 and 35].…”
Section: Discussioncontrasting
confidence: 55%
“…These results are consistent with granulins’ pro-inflammatory properties and with progranulin’s ability to promote tissue repair. Recently, circulating progranulin was shown to exist as homodimers [18] . It remains to be determined how dimerization affects progranulin’s binding to SLPI, susceptibility to cleavage, or overall function.…”
Section: The Search For Progranulin Receptors and Binding Proteinsmentioning
confidence: 99%
“…These findings sparked considerable interest since HDL’s beneficial effects are believed to be, in part, due to its anti-inflammatory properties [78] . However, subsequent studies using several methods of HDL isolation [18] and two proteomic studies [79, 80] did not detect progranulin in human or mouse HDL. Thus, a direct link of progranulin to HDL seems unlikely.…”
Section: Progranulin May Modulate Processes Involved In Atherosclerosismentioning
confidence: 99%
“…Already it has been shown that the delipidation with specific organic solvents described in this review does not adversely affect these new proteins associated with the lipoprotein fractions. In fact, the delipidation procedure has been applied to help identify the novel proteins, which are associated with the lipoprotein fractions in plasma [49][50][51] whereas, a different solvent system consisting of diethyl ether:methanol caused denaturation and precipitation of the delipidated HDL particles [52].…”
Section: Delipidation and The Effects Of Forward Transport Of Lipids mentioning
confidence: 99%